Didactic sequence for the teaching of gravitational waves and interference in high school (Research, Society and Development, 2020)
This work leads a suggestion of teaching gravitational waves and interference, for high school students through the application of a didactic sequence elaborated in line with David Ausubel's theory of Significant Learning and the Biggs and Tang constructive alignment theory. It is the analysis of the application of an didactic sequence designed to facilitate teaching work from planning to the execution of actions and assessment of physics learning, thus serving as motivation for the production of new sequences, built by the teachers themselves, taking into account the appropriation of this tool as an archetype. It is a field research and gathers a series of activities, inside and outside the classroom, systematically prepared and organized to achieve the preliminary proposed learning objectives, and uses mechanisms such as experimentation and use of ICTs, giving the student a more active and autonomous role in the construction of learning itself, making it more efficient and meaningful, which is the intended result.